The Early Frankfurt School and Religion
X, 263 p.
Keywords: Are religions tissues of superstition and repression, or repositories of the highest hopes and aspirations of humanity, or perhaps both at the same time? For many of those thinkers who lived through the horrors and upheavals of the first half of the twentieth-century, this old question acquired a new urgency. This volume examines the ways in which the authors of the early Frankfurt School criticized, adopted and modified traditional forms of religious thought and practice. Focusing on the works of Theodor W. Adorno, Walter Benjamin, Erich Fromm, Max Horkheimer, Otto Kirchheimer and Franz Neumann, it analyzes the relevance of religious traditions and of the Enlightenment critique of religion for modern conceptions of emancipatory thought, art, law, and politics.